1985
DOI: 10.1002/path.1711450305
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical studies of c‐reactive protein and apolipoprotein b in inflammatory and arterial lesions

Abstract: Interactions in vivo between C-reactive protein (CRP) and apolipoprotein B (apo-B)-containing lipoproteins were sought in inflammatory lesions and atherosclerosis. CRP was demonstrated immunohistochemically on the surface of some muscle fibres in locally induced inflammatory lesions in the rabbit, but apoB was not detected in the same distribution. CRP was not detected in catheter-induced aortic endothelial injuries in the rabbit, in arterial lesions containing apoB from cholesterol-fed rabbits, in apoB-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…High concentrations of CRP have been measured in atherosclerotic plaques [41][42][43]. This is consistent with high levels of complement 3 also seen in these plaques reviewed - [62].…”
Section: Crp and Atherosclerosissupporting
confidence: 63%
“…High concentrations of CRP have been measured in atherosclerotic plaques [41][42][43]. This is consistent with high levels of complement 3 also seen in these plaques reviewed - [62].…”
Section: Crp and Atherosclerosissupporting
confidence: 63%
“…4,16,17 Some authors reported positive staining for CRP in aortic lesions 16,17 and some did not. 15 The possibility that these contradictory observations reflect differences in the efficiency of the antibodies to detect CRP cannot be excluded. CRP may undergo structural changes (eg, oxidation or aggregation) at sites of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, the molecule was extracted from and quantified in human aortic atherosclerotic intima, thus providing the first evidence for its presence in atherosclerotic lesions. 4 In an attempt by Rowe et al 15 to localize CRP in atherosclerotic lesions, no CRP could be demonstrated. In contrast, Reynolds and Vance 16 and Hatanaka et al 17 were able to demonstrate CRP in atherosclerotic lesions of human aortas, and both reported that CRP was localized around foam cells and the deep fibroelastic layer and in the fibromuscular layer adjacent to the media.…”
mentioning
confidence: 99%
“…Indeed human CRP passively administered to mice alters in favour of the spleen the balance of splenic and hepatic uptake of pneumococci, of C-polysaccharide-coated mouse erythrocytes and of free C-polysaccharide, although the overall blood clearance rate of these ligands is not affected (3,33,37,38 (48,49) or essential controls for immunological specificity omitted (48). Significant CRP is present only rarely at sites of inflammation per se, although it definitely does appear in small amounts on frankly necrotic muscle fibres in cardiac or skeletal muscle damaged by extreme experimental procedures (3,43,44,50). The present failure to detect significant tissue deposition of 1231I-CRP in any of the various pathologies studied is therefore compatible with the paucity of convincing immunohistochemical evidence, but we cannot exclude the possibility that avid binding of autologous CRP to potential tissue ligands at an early stage ofdisease may have blocked their subsequent availability for interaction with the tracer.…”
Section: Discussionmentioning
confidence: 99%